PENGEMBANGAN MODEL GOOD CORPORATE CULTURE BERBASIS SPIRITUAL BRAND (NILAI SPIRITUAL) DI PT. BANK SYARIAH MANDIRI JAWA TIMUR - Mohamad Djasuli (InFestasi, 2008)
This research is aim to try monitoring the weakness ofCorporate Culture Bank Syariah Mandiri (BSM) as mention before,by replying and recommendation high values of Spiritual Brandwhich has strong dominated to all the BSM employees also to followthe future development of ideal Spiritual Brand by pre-reductionfrom the employee arrangement values and market demand.The research is using type of device research with descriptiveresearch and qualitative research. The research location was atBSM Branch Office Surabaya, Gresik, Sidoarjo, Mojokerto, Malang,and Pasuruan, by using one key information of bank with 50Informants. Technique data was using questionnaire, observationand interview.In course of assessment showed there are values corporate of SIFATdominant and the mean have been owned by the strength expandin community of BSM. That dominant values represent excellenceof competitive for BSM in present culture values and condition offuture cultural values.Those Dominant values is Siddiq : Intention, Sincerity,independence, patient, Istiqomah, Vision, Openness, Continuity,Risk, Optimism, Fhatanah, Science, Professionalism, Achievement,Amanah, Responsibility, Analysis, harmonious, Objective,Carefulness, Tabliq, Tolerance, Cooption, Team work.